Regional energy transition governance for the co-transformation of sustainable energy infrastructure as a public service in rural areas - Kelly, Ryan; Mbah, Melanie (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
The urgent transformation of our energy system towards a sustainable infrastructure of public services regularly fails in regional implementation due to spatial and social requirements of rural areas. Using the example of a transdisciplinary project, this paper identifies dilemmas in the participatory implementation of the regional energy transition and formulates conditions for the success of a spatially sensitive energy transition governance. As shown by the governance approach developed for “co-transformation”, context-sensitive forms of participation in co-regulation, co-allocation and co-visioning can contribute to procedural, distributional and future justice and thus to the acceptability of the regional energy transition as a public service infrastructure in rural areas. Central fields of action are open-ended and regionally adapted forms of participation through co-regulation in the planning process, approaches to spatial co-allocation of energy transition-related burdens and local added values, as well as the co-visioning of regional energy futures and regional energy visions to be derived from them.